2021
DOI: 10.4314/jcmphc.v33i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Male Involvement in Family Planning: A Qualitative Survey of the Barriers and Facilitators amongst Married Men in Sokoto metropolis

Abstract: Background: Although large families are desired in Nigeria, women tend to want fewer children than men but are often unable to limit or space childbirth due to gender dynamics within relationships. Studies have identified men as a significant barrier to the use of  contraceptives by their wives. The study explored married men’s knowledge and perception on family planning (FP), involvement in FP, barriers and facilitators of male involvement (MI) in FP in Sokoto Metropolis.Methods: A qualitative study was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The design of the VFPC and bulk SMS to target household heads, which was done to improve spousal consent for FP services aligns with recommendations of studies that have suggested male involvement in FP services to boost uptake. 38 , 39 The design of the project to engage religious and community leaders, especially in Northern Nigeria, has been an effective strategy for improving the uptake of modern contraceptive services in Nigeria. 40 All of these contributed to the success of the LUPSS project.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the VFPC and bulk SMS to target household heads, which was done to improve spousal consent for FP services aligns with recommendations of studies that have suggested male involvement in FP services to boost uptake. 38 , 39 The design of the project to engage religious and community leaders, especially in Northern Nigeria, has been an effective strategy for improving the uptake of modern contraceptive services in Nigeria. 40 All of these contributed to the success of the LUPSS project.…”
Section: Discussionmentioning
confidence: 99%